Theoretical and Practical Aspects Revaluation of Fixed Assets - Савчук, Т. В.; Мeдвідь І. Б.; Негрич, І. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
The main reasons of realization of overvalue are considered. The necessity of realization of overvalue of assets is substantiated. The advantages and disadvantages of a model of account of inconventible (або inconvertible) assets are mentioned, and also is mentioned the basic moments of discount policy, that select by enterprise at electing of this modal account. The comparative analysis of existent manners is conducted to realization and reflection of overvalue of inconvertible assets in National Accounting Standarts 7,8 and IAS 16. The peculiarities of overvalue completely depreciated assets are separately underlined. The differences in a reflection of the account of result first and next overvalues are separately investigated. The basic features of realization of overvalue are illustrated on certain examples. The attention is assented on influence of the conducted overvalue on further depreciatiation of assets, in particular, on the calculations of depreciation at presense of liquidating value. The values to research add resulted examples of the stage-by-stage writing of sum of previous revaluation, and also made conclusions about the consequences of realization of overvalue of the assets for an enterprise.